Association between structural and biochemical changes in the brain and chronic pain - An integrative review (Research, Society and Development, 2025)
The present study aimed to analyze the structural and biochemical changes in the brain associated with chronic pain, synthesizing recent findings through an integrative literature review. The research was conducted in electronic databases such as PubMed, SCOPUS, SciELO, and ScienceDirect, covering publications from 2014 to 2024. Descriptors related to chronic pain and brain changes were used, combined with Boolean operators. The results revealed that chronic pain is associated with functional and structural changes in the brain, such as a reduction in gray matter volume in the dorsolateral prefrontal cortex and increased functional connectivity in areas related to emotional modulation and pain processing. Additionally, pain experience was described as subjective, with unique neural patterns for each patient, reinforcing the importance of individualized therapeutic approaches. It was concluded that chronic pain involves maladaptive neuroplasticity, affecting critical brain regions for emotional regulation, pain processing, and cognitive functions. Interventions such as neuromodulation and cognitive-behavioral therapy appear promising. These findings highlight the need for integrative and personalized therapeutic strategies, as well as longitudinal studies to deepen the understanding of underlying mechanisms.